Objectives of Extension Education- An analysis of Perception of KVK Professionals - Prashish Singh, Prashish Singh; Basavaprabhu Jirli; Kalyan Ghadei; Priyanka Roy; Jagriti Kumar (Indian Journal of Extension Education, 2023)
Krishi Vigyan Kendra provides training to various stakeholders as a means of delivering technology. The study was conducted in March-August, 2021 using a structured questionnaire that included a random sampling of 150 KVK scientists over 145 KVKs from 24 states & Union territories. The study assesses the perception of the KVK professionals towards the objectives of Extension. This perception towards objectives is measured by using 5 point continuum on Likert scale using  31 statements. Communicating the research information scored first rank with 66.67 weighted mean score and also revealed that the majority of KVK professionals were having favorable perceptions regarding objectives (74.67 %) of extension followed by 12.66 % were having both highly favorable & unfavorable perceptions towards objectives of extension. Additionally, it was shown that information-seeking behaviour had a positively significant relationship towards the perception of KVK professionals for the objective of extension education. Step-wise regression model also used to identify significant variance contributors in which information-seeking behavior contributed about 2.70 percent of the total variances in perceptions toward extension objectives. Therefore, KVK professionals need to change their unfavourable to favourable perceptions towards the objective of extension for making KVK programs more successfully.